Whole exome sequencing identifies a novel compound heterozygous GFM1 variant underlying developmental delay, dystonia, polymicrogyria, and severe intellectual disability in a Pakhtun family. Issue 9 (15th June 2022) - Khan, Atta Ullah; Khan, Ibrar; Khan, Muhammad Ismail; Latif, Muhammad; Siddiqui, Muhammad Imran; Khan, Shafi Ullah; Htar, Thet Thet; Wahid, Ghazala; Ullah, Ikram; Bibi, Fehmida; Khan, Asifullah; Naseer, Muhammad Imran; et al.
Abstract: Mitochondrial protein synthesis requires three elongation factors including EF‐Tu ( TUFM ; OMIM 602389), EF‐Ts ( TSFM ; OMIM 604723), and EF‐G1 ( GFM1 ; OMIM 606639). Pathogenic variants in any of these three members result in defective mitochondrial translation which can impart an oxidative phosphorylation (OXPHOS) deficiency. In this study, we investigated a consanguineous Pakhtun Pakistani family. There were four affected siblings at the time of this study and one affected girl had died in infancy. The index patient had severe intellectual disability, global developmental delay, dystonia, no speech development, feeding difficulties, and nystagmus. MRI brain presented thinning of corpus callosum and polymicrogyria. Whole exome sequencing revealed a novel compound heterozygous variant in GFM1 located on chromosome 3q25.32. Sanger sequencing confirmed recessive segregation of the maternal (NM_001308164.1:c.409G > A; p.Val137Met) and paternal (NM_001308164.1:c.1880G > A; p.Arg627Gln) variants in all the four affected siblings. These variants are classified as "likely‐pathogenic" according to the recommendation of ACMG/AMP guideline. GFM1 alterations mostly lead to severe phenotypes and the patients may die in early neonatal life; however, four of the affected siblings had survived till the ages of 10–17 years, without developing any life‐threatening conditions. Mostly, in cousin marriages, the pathogenic variants are identical‐by‐descent, and affected siblings born to such parents are homozygous. Three homozygous variants were shortlisted in the analysis of the WES data, but Sanger sequencing did not confirm their segregation with the disease phenotype. This is the first report from Pakistan expanding pathogenicity of GFM1 gene.